A VPS33B CRISPR knockout study: In vitro evidence of an adhesion defect - Maria Caluianu; Kimberley A. Owen (PLoS ONE, 2026)
VPS33B is a ubiquitously expressed regulator of vesicular membrane fusion and protein sorting involved in a broad range of cellular functions from organelle biogenesis to the establishment of apicobasal polarity. Loss-of-function mutations in VPS33B cause arthrogryposis–renal dysfunction–cholestasis (ARC) syndrome, a rare autosomal recessive disorder with multi-organ involvement, including a characteristic proximal tubular dysfunction in the kidney. While VPS33B has been studied in several cell types, its role in proximal tubular epithelial cells remains poorly understood. To investigate its function, a proximal tubular cell line (RPTEC-TERT1) was CRISPR-edited to generate VPS33B knockout (KO) cells. These cells were characterised using brightfield imaging, immunostaining, RNA sequencing, and cell detachment assays, revealing a distinct ‘peeling’ phenotype and altered adhesion properties. Transcriptional profiling indicated changes in genes linked to cell adhesion. Together, these findings offer preliminary evidence that loss of VPS33B impairs cell–matrix attachment and reveal the first insights into the role of VPS33B within proximal tubular epithelial cells.